(untitled) (Current Problems in Rail Vehicles, 2025)
Railpool is one of Europe’s market leaders in the field of traction rail vehicle leasing, including responsibility for their maintenance. Ensuring safe operations across a number of European countries presents a number of challenges and risks, that need to be compensated for by appropriate means of maintenance organisation. One of the significant factors in international traffic is the different wear of the wheel profiles. Examples of infrastructure with critical development are used to show the differences in the nature of the wheel profile wear and their influence on vehicle operation and maintenance.